Stenocarpella chrysopogonis, a New Species Causing Leaf Streak Disease of Chrysopogon zizanioides in Southern China - Jia, Xitao (Plant disease, 2023)
Vetiver grass (Chrysopogon zizanioides) has been widely used in recent years for ecological environment management, restoration of degraded ecosystems, and essential oil extraction. In 2019, a leaf streak disease of C. zizanioides was observed in Zhanjiang, Guangdong Province, China. The disease appeared as large streak lesions on the leaves, on which conidiomata were formed. A pathogenicity test with the fungus isolated from these lesions confirmed Koch's postulates and thus the fungus as the causal agent of this disease. A morphological resemblance of the pathogen to Stenocarpella was noted upon microscopic examination. Phylogenetic trees inferred from both individual and combined ITS, LSU, and tef1 sequences confirmed the pathogen as a species of the Diaporthaceae and revealed it to be closely related to Phaeocytostroma and Stenocarpella species. As morphological characters clearly placed the pathogen in the genus Stenocarpella, it was described as S. chrysopogonis